Adaptive Power Control of VSC-HVDC as a Corrective Measure - Raab, Alexander; Frauenknecht, Dominik; Riebesel, David; Mehlmann, Gert; Luther, Matthias (2021 IEEE THE 4TH INTERNATIONAL CONFERENCE ON POWER AND ENERGY APPLICATIONS (ICPEA 2021), 2021)
This paper provides a novel control approach for Voltage Source Converter High Voltage Direct Current systems (VSC-HVDC) based on the voltage angles between the points of common coupling (PCC). The control aimed at an automatic relief of the parallel lines in case of disturbances as well as an increase of the transient stability. The basic principle of the control system and its integration into classic VSC-HVDC control concepts were described. An implementation of the voltage angle control (VAC) and the HVDC model for transient stability studies were presented. Simulations were carried out in a modified Nordic Test System with an additional HVDC integration, where the methods of using a droop-based AC-emulation control (ACE) and the VAC with PI-controllers were analyzed. Simulations showed that HVDC systems with Droop control (ACE) only take over a part of the failed power flow despite corresponding transmission reserve, whereas PI control (VAC) could take over the entire power flow. The HVDC systems could automatically compensate parallel lines in the event of a disturbance and improve power system stability.<br
CRIS-Team WoS Importer:2022-03-25
Keywords: Active power flow; transient stability; voltage angle; VSC-HVDC